Saliva as a Biological Sample for COVID-19 Diagnosis? - Kafle, D.; Sapkota, D. (Kathmandu University Medical Journal, 2020)
The COVID-19 pandemic, caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), has become a severe global health problem affecting almost every country in the world. Compared to other coronaviruses, SARS-CoV-2 is considered to be more infectious thereby leading to a rapid spread of this disease across the world. The effective control of this disease relies on timely diagnosis, proper isolation, contact tracing of the infected people and segregation of vulnerable group from potential contamination. Currently, the gold standard diagnostic test for COVID-19 is real-time reverse transcriptase polymerase chain reaction (RT-PCR) using nasopharyngeal swab (NPS). However, NPS collection has several shortcomings. Besides requiring an active involvement of healthcare personnel and personal protective equipment (PPE), NPS collection is uncomfortable for the patient as it can induce coughing, gagging, vomiting and even bleeding. Evidence from current studies indicates that saliva has a potential to be useful as an alternative biological sample for COVID-19 diagnosis. Indeed, saliva as a biological sample offers several advantages over NPS. Saliva collection is better accepted by patients, it can be self-collected and does not require PPE and active involvement of healthcare personnel. Moreover, preliminary results indicate that the sensitivity and specificity of saliva for COVID-19 diagnosis is similar to that of NPS. This summarizes recent observations in the field and discusses the potential use of saliva for COVID-19 diagnosis.